Ascidians Outbreak: A Threat For Coral Reefs in Panjang Island, Jepara - Dwi Haryanti; Diah Permata Wijayanti; Bambang Yulianto; Mada Triandala Sibero; Lutfillah Arief Ghinaa Shabrina (Universitas Diponegoro, 2021)
Eutrophication and sedimentation have become a major threat to coral reefs in nearby areas with anthropogenic activities. These threats are often accompanied by shifting ecosystems from coral-rich to fast-growing algae-dominated water, and high prevalence of coral disease. In Panjang Island, Jepara, we observed the outbreak of photosynthetic ascidians along with a high sedimentation at the eastern part of the island. The ascidians were seen overgrowing most substrates including corals, macroalgae, dead-coral-algae, and rubbles in April to May 2019. In July and August 2019, observation and data collection using quadrant transect were conducted to monitor the outbreak. The result showed that ascidians were still present in the area, despite becoming pale and smaller. This report shows that the outbreak of these photosynthetic ascidians was not persistent, however, the effect on coral reef health should not be overlooked.